The Pragmatics of Interruption: A Comparative Analysis of Gender Differences in English and Arabic Conversations - Ulla Kamal Ismael (JURNAL PENDIDIKAN BAHASA, 2025)
This study explores the complex dynamics of interruption in conversations, with a particular focus on gender differences within English and Arabic linguistic contexts. As a widely observed conversational feature, interruption reveals underlying power dynamics and social roles shaped by cultural norms. The researcher applies a mixed-methods approach, combining both quantitative and qualitative analyses of recorded conversations from English and Arabic-speaking communities. The findings highlight notable variations in interruption patterns between the two languages, uncovering distinct cultural and linguistic practices. Through a comparative lens, this study offers a nuanced understanding of how gender influences the frequency, types, and functions of interruptions, thereby enriching the field of pragmatics and contributing to the broader discourse on gendered communication.